From Serious Shortage of Researchers to OHS Law Changes and Growing Industrial Needs: A Dynamic and Quiet Force - Nadeau, Sylvie; Fatisson, Julien; Badri, Adel; Emami-Mehrgani, Behnam (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2013)
SummaryScientists having raised concerns about technological advancements and the associated risks, the Quebec scientific community implemented the work safety component within the Quebec Occupational Health and Safety Research Network (QOHSRN). This initially fostered a first geographical connection among scientists, thus facilitating knowledge exchange and transfer. With various research themes, the first component members made an initial observation of the critical situation in regard to occupational safety in the industrial sector. Yet, occupational safety is a shared concern affecting all industrial sectors, environments and countries. The strategic occupational safety component expanded its efforts toward internationalization to increase the visibility of its activities. The creation of components within other global networks and a journal were the first steps marking this desire for international sharing. With the number of environments affected by occupational health and safety (OHS), research activities in this field involve an interinstitutional and interdisciplinary research community. The QOHSRN’s strategic occupational safety component leads by example by involving researchers from all fields of study and various Quebec universities and research institutions. Research themes within the component are all equally diverse and complementary. They range from the study of occupational safety integration methods at the design stage to technical, organizational, normative, legislative and preventive methods, and the development of new protection devices and equipment. A portrait of the make-up of the QOHSRN’s strategic occupational safety component and its evolution from its creation to the QOHSRN’s 10th anniversary was also produced and analyzed to show its growing evolution.